Looking into the black box of "medical progress": Rising health expenditures by illness type and age - Friedrich Breyer; Normann Lorenz; Gerald J. Pruckner; Thomas Schober (Johannes Kepler Universität Linz, Christian Doppler Laboratory Aging, Health and the Labor Market, 2021)
There is agreement among health economists that on the whole medical innovation causes health care expenditures (HCE) to rise. This paper analyzes for which diagnoses and in which age groups HCE per patient have grown significantly faster than average HCE. We distinguish decedents (patients in their last four years of life) from survivors and use a unique dataset comprising detailed HCE of all members of a regional health insurance fund in Upper Austria for the period 2005-2018. Our results indicate that among decedents in particular the expenditures for treatment of neoplasms have exceeded the general trend in HCE. This confirms that medical progress for this group of diseases has been particularly strong over the last 15 years. For survivors, we find a noticeable growth in cases and cost per case for pregnancies and childbirth and also for treatment of mental and behavioral disorders. The pattern of expenditures over age groups shows that among decedents the younger age groups (below 75) exhibit both the highest HCE per capita and the highest expenditure growth over time. For survivors, we find a steady increase in annual per capita HCE over age in both sexes, but the highest growth rates are observed in the age groups between 20 and 50 years.
Keywords: H51; J11; I19; 330; health care expenditures; medical progress; cost of dying